Use of climate change scenarios for building simulation : the CIBSE future weather years. (TM (Chartered Institution of Building Services Engineers), 2009)
Climate change has become a reality and further and accelerating change is expected over the next few decades. It is likely that the UK will experience milder winters and hotter and more extreme summers. These changes will impact on building performance, particularly with regard to cooling and ventilation, with implications for the quality of the indoor environment, energy consumption and carbon emissions. Assessment of these factors at the design stage is currently based on computer simulations made using historical weather data. Such simulations are fundamentally limited therefore in their ability to provide a true picture of future performance: it is possible that a generation of buildings are being constructed that will cope poorly with the demands that future climate will place on their envelopes, interior spaces and systems. There are also important questions regarding existing buildings - how, when and to what extent they will need to be adapted to cope with future climate change. --